Wire rope isolators for seismically base-isolated lightweight structures: Experimental characterization and mathematical modeling. (1st June 2017) - Vaiana, Nicolò; Spizzuoco, Mariacristina; Serino, Giorgio
Highlights: Wire Rope Isolators (WRIs) are experimentally investigated for use in isolation systems. WRIs are tested in three displacements ranges for different values of vertical load. An efficient 1d Nonlinear Exponential Model is proposed. The proposed model is able to simulate the increase of the tangent stiffness. Abstract: The results of an extensive series of dynamic and static experimental tests conducted on four Wire Rope Isolators (WRIs) under different values of vertical load are presented. The main aim of this work is identifying the mechanical characteristics of WRIs in three displacements ranges, that is, small, relatively large and large displacements ranges, to allow the use of these metal devices in the base isolation system of seismically base-isolated lightweight structures. In order to simulate the dynamic behavior of WRIs in the two principal horizontal directions, namely, Roll and Shear directions, a one dimensional (1d) Nonlinear Exponential Model, able to simulate the increase of the tangent stiffness observed at larger displacements, is proposed. Compared to the widely used Bouc-Wen model, the proposed one does not require the numerical solution of a first order ordinary nonlinear differential equation, thus decreasing the computational effort of nonlinear time history analyses, and contains a smaller number of parameters to be identified. The mathematical model has been validated by comparing the experimental hysteresis loops obtained during cyclic tests with those predicted analytically.